Measuring mineral dissolution kinetics using on-line flow-through time resolved analysis (FT-TRA): an exploratory study with forsterite - De Baere, Bart; François, Roger; Mayer, K. Ulrich (Chemical geology, 2015)
We explore the applicability of on-line flow-through time-resolved analysis (FT-TRA) to measure mineral dissolution rates, determine dissolution rate parameters, and monitor dissolution stoichiometry under both constant and transient eluent conditions. A custom-built automated flow-through system is used to subject mineral samples to controlled eluent flows of constant or varying composition, and the dissolution products are measured on-line with a quadrupole ICP–MS. Because forsterite dissolution has been extensively studied, this mineral provides an ideal benchmark to test the approach. FT-TRA has several advantages compared to the mixed-flow reactors conventionally used to measure mineral dissolution. The mineral dissolution regime (surface vs transport-controlled) can be readily established prior to conducting dissolution experiments, which is important if the goal of the experiment is to determine dissolution rate parameters. Because of the small volume (25μL) of the flow-through reactor, the time to reach steady state concentration in the effluent is shorter and is limited by the intrinsic properties of the mineral, instead of the residence time of the effluent in the reactor. For minerals reaching steady-state dissolution rapidly, dissolution rate parameters (rate constant(s) and reaction order(s)) are established in a few hours, allowing for replications, statistical analysis of the results, and investigation of the underlying causes of variability. The experimental set-up can be adapted for minerals that require longer periods of time to reach steady-state dissolution. In addition, FT-TRA lends itself particularly well for detailed monitoring of dissolution rates and dissolution stoichiometry under transient conditions. For forsterite dissolution under acidic conditions, preferential release of Mg when pH transits to lower values, and preferential release of Si when pH transits to higher values is clearly documented and can be interpreted as indicating changes in the mean depth of the Si-rich surface layer in response to changes in eluent acidity. Episodes of exfoliation of the Si-rich surface layer can also be identified, providing a means to study one of the potential rate limiting steps for CO2 sequestration by carbonation of olivine. The results presented here indicate that FT-TRA with online ICP–MS analysis could be a useful and multifaceted addition to the toolbox available to study mineral dissolution. •We explore the use of FT-TRA as a tool to measure mineral dissolution rates using forsterite as a test case•FT-TRA can be used to determine the dissolution regime prior to measuring mineral dissolution rates•The high surface area to volume ratio provides a fast way to measure mineral dissolution rate parameters•FT-TRA documents gradual (leached layer) and abrupt (exfoliation) changes in mineral surface composition